2020
DOI: 10.1371/journal.pone.0241918
|View full text |Cite
|
Sign up to set email alerts
|

Immunoproteomic analysis of Trichinella spiralis and Trichinella britovi excretory-secretory muscle larvae proteins recognized by sera from humans infected with Trichinella

Abstract: The present study compares the immunogenic patterns of muscle larvae excretory-secretory proteins (ML E-S) from T. spiralis and T. britovi recognized by Trichinella-infected human sera. Samples were analyzed using two-dimensional electrophoresis (2-DE) coupled with 2D-immunoblot and liquid chromatography-tandem mass spectrometry LC-MS/MS analysis, two ELISA procedures and a confirmatory 1D-immunoblot test. Sera were obtained from nine patients with a history of ingestion of raw or undercooked meat who presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…It should be noted, however, that all global studies on the use of Western blot for pig trichinellosis detection were performed using T. spiralis ML ES antigens as well as serum samples collected from pigs infected with T. spiralis [30,31]; the results of this research have been discussed elsewhere [32]. It was also proved that all Trichinella species share some ES proteins and, as a consequence, an ES antigen obtained from one Trichinella species is able to detect infections induced by other Trichinella species and genotypes [29]; however, recently Grzelak et al [33] showed that sera from Trichinella-infected persons displayed some differences in terms of their speci c band patterns when T. spiralis and T. britovi ML ES antigens were used. It was also found by using one-dimensional electrophoresis that the native T. spiralis ES antigen shows more protein bands than the T. britovi ML ES antigen [33].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…It should be noted, however, that all global studies on the use of Western blot for pig trichinellosis detection were performed using T. spiralis ML ES antigens as well as serum samples collected from pigs infected with T. spiralis [30,31]; the results of this research have been discussed elsewhere [32]. It was also proved that all Trichinella species share some ES proteins and, as a consequence, an ES antigen obtained from one Trichinella species is able to detect infections induced by other Trichinella species and genotypes [29]; however, recently Grzelak et al [33] showed that sera from Trichinella-infected persons displayed some differences in terms of their speci c band patterns when T. spiralis and T. britovi ML ES antigens were used. It was also found by using one-dimensional electrophoresis that the native T. spiralis ES antigen shows more protein bands than the T. britovi ML ES antigen [33].…”
Section: Discussionmentioning
confidence: 91%
“…It was also proved that all Trichinella species share some ES proteins and, as a consequence, an ES antigen obtained from one Trichinella species is able to detect infections induced by other Trichinella species and genotypes [29]; however, recently Grzelak et al [33] showed that sera from Trichinella-infected persons displayed some differences in terms of their speci c band patterns when T. spiralis and T. britovi ML ES antigens were used. It was also found by using one-dimensional electrophoresis that the native T. spiralis ES antigen shows more protein bands than the T. britovi ML ES antigen [33]. However, on the basis of our results and studies conducted by Gomez Morales et al [30], it should be stated that the use of T. britovi ML ES antigen and serum samples of pigs infected with T. britovi did not signi cantly affect on Western blot band pattern as compared to the pattern generated by serum of pigs infected with T. spiralis tested by using T. spiralis ES-WB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, previous immunoproteomic studies have identified hypothetical protein Tsp_10331 (XP_003372574.1), conserved hypothetical protein (XP_003374582.1), putative LNS2 protein (OUC42377.1), hypothetical protein D917_07875 (OUC46244.1), peptidase S1C family (XP_003375617.1), phosphatidylinositol phosphatase PTPRQ (KRY42983.1) and putative zinc finger protein C06E1.8 (KRY37548.1) as T . spiralis antigens [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Trichinella species. Immunoproteomic studies of Trichinella spiralis , Trichinella pseudospiralis and Trichinella britovi have focused on ES proteins [ 51 , 52 , 53 , 54 , 55 ], with the intention of improving the immuno- or sero-diagnosis of trichinellosis. Numerous immunogenic proteins, including serine protease, enolase and peptidase inhibitors, were recognised by antibodies in the sera from patients or from experimental animals.…”
Section: Recent High-throughput Proteomic Explorations Of Parasitic Nematodesmentioning
confidence: 99%